Navigating uncertainty: parental agency in Kansan Chinese families’ education at home during the pandemic - Yin, Danqing (Frontiers in Education, 2025)
This study examines the experiences of five Kansan parents who took on a key role in their children’s home education during the pandemic. The author uses online interviews to investigate how parental agency is manifested through parents’ actions regarding children’s education and health. Drawing inspiration from Bandura’s theory on human agency, the study applies four core properties of agency: intentionality, forethought, self-reactiveness, and self-reflectiveness. The discussion connects the findings to the broader literature on agency, offering insights into how families navigate challenges and support children during crises such as the pandemic.